The Prevalence of Huayan-Chan 華嚴禪 Buddhism in the Regions of Northern China during the 11th Century: Focusing on Chinese Language Texts from the Song, Liao and Xixia (Tangut) Kingdoms - Wang (王頌), Song (Journal of Chan Buddhism, 2019)
Abstract In the 11th century, the dissemination of Buddhism in the territories of Northern Song 北宋 dynasty (960–1127) China, Khitan 契丹 Liao 遼 (907/916–1125), and Xixia 西夏 (Tangut 党項, 1038–1227) kingdoms each reached a peak. What united the learned peoples of these three kingdoms in terms of religious and intellectual development was the comparatively widespread study and adoption of the teachings of Huayan Buddhism, or studies of and commentaries to the translations of the Avataṃsaka-sūtra into Chinese in 60-, 80-, and 40-rolls ( Huayan jing 華嚴經, esp. T nos. 278, 279, 293). In this article I address some of my earlier research concerning two treatises composed by Bensong 本嵩 (active ca. 1083–1085), the Huayan guan tongxuan ji 華嚴觀通玄記 (Record of the Profundities of Total Meditative Insight [or Contemplation] of the Gaṇḍavyūha chapter of the Avataṃsaka-sūtra Flower Garland Sūtra) and Fajie guan sanshimen song 法界觀三十門頌 (Verses Praising the Thirty Contemplative Approaches or Gates presented in the Gaṇḍavyūha Chapter on Entry into the Realm of Reality), among other examples from the period, to illustrate how these Huayan teachings were actually the product of Huayan and Chan Buddhist ideological frameworks, which fruitfully can be called Huayan-Chan. In order to demonstrate why the rubric ‘Huayan-Chan’ can be productive, I examine a range of commentarial Buddhist texts in Chinese to show who the patriarchs of Huayan-Chan were considered to be during the 11th century across the ethnically and linguistically diverse region of Northern China, and bring to the fore what some of these key teachings were. My main goal is to present the specific circumstances within which Huayan-Chan developed within the three kingdoms of Northern Song China, the Khitan Liao, and the Tangut Xixia.